Fermentation optimization and pilot production of Bacillus subtilis ZY1 producing CpxP - Rongrong DONG; Huan ZHANG; Xinran YU; Hao LIU; Xiaohui ZHOU (Journal of Hebei University of Science and Technology)
In order to obtain the optimal conditions for liquid fermentation of Bacillus subtilis ZY1 producing CpxP protein and prepare microecological bactericides, the fermentation process of Bacillus subtilis ZY1 was optimized by single factor test and response surface test. The results show that the optimal carbon source, nitrogen source and inorganic salt of fermentation medium are starch, soybean meal and NaCl, respectively. The optimal medium formulation is starch at 2.12 g/L, soybean meal at 5.90 g/L, and NaCl at 5.21 g/L, with a viable bacteria count of 9.63×108 CFU/mL, which is 11.04 times higher than that before the medium optimization. The optimum initial pH value, temperature, rotation speed and inoculation amount for shake flask fermentation are 7.0, 37 ℃, 200 r/min and 2%, respectively. The viable bacteria number is 1.05×109 CFU/mL, which is 9.0% higher than that of optimized medium. During the pilot production process of the microecological bactericides based on 5 t fermentation tank system with 10% inoculated quantity, the count of viable ZY1bacteria reaches 1.05×1011 CFU/mL, which is 100 times higher than that after shaker optimization. When the spore rate reaches 90% at the end of fermentation, 1 012 kg bactericides are prepared by spray drying, and the count of viable bactericide is 8.5×109 CFU/g. The research results can provide basic materials for further research on the biocontrol function of CpxP protein in animal bacterial diarrhea disease.